A description of local pig feeding systems in village smallholder farms of Western Kenya - Mutua, Florence K.; Dewey, Catherine E.; Arimi, S.M.; Ogara, W.; Levy, M.; Schelling, E. (Springer, 2012)
We used face-to-face interviews to gather data on pig feeding practices in rural Busia District, Kenya. We visited 164 pig farms three times in the course of the study period. The pigs were weighed in kilograms during the visits. Feeds offered to pigs were described during the interviews. The most frequently fed feedstuffs were; ground maize or “ugali” (88%), kitchen leftovers (83%) and dried fish locally called “omena” (78%). Farmers provided pigs with water separately from the feeds. Sweet potatoes, “ugali” and cassava were available and could serve as good sources of energy for pigs in the district. Fruits and vegetables were also available and could potentially act as good sources of vitamins. Sweet potato vines, “omena” fish and slaughter blood were available and could provide pigs with proteins. The average daily gain (ADG) for pigs ≤5 months of age, pigs of 5.1–9.9 months of age and pigs of ≥10 months old was 94.5 (±43), 127 (±49.8) and 99 (±92) g, respectively (p = 0.000). This study has outlined the different local pig feeds available in Busia district. We recommend two things: first, additional research on nutrient composition for the identified local feeds, and second, developing and validating simple local feed combinations that would achieve balanced local pig rations.